2014
DOI: 10.15252/embj.201489652
|View full text |Cite
|
Sign up to set email alerts
|

Receptor guanylyl cyclase‐ G is a novel thermosensory protein activated by cool temperatures

Abstract: Transmembrane guanylyl cyclases (GCs), with activity regulated by peptide ligands and/or calcium-binding proteins, are essential for various physiological and sensory processes. The mode of activation of the GC subtype GC-G, which is expressed in neurons of the Grueneberg ganglion that respond to cool temperatures, has been elusive. In searching for appropriate stimuli to activate GC-G, we found that its enzymatic activity is directly stimulated by cool temperatures. In this context, it was observed that dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 49 publications
3
57
0
1
Order By: Relevance
“…These results suggest that Sey/+ pups born from young father exhibit less vocalization when isolated from their mother and littermates; the phenotype was not obvious in Sey/+ pups born from aged father due to the decreased number of USV calls that occur also in WT littermates. Since USV in pups is considered to be a mother call related to anxiety and perception of temperature [54, 55], Sey/+ pups born from young father may exhibit a lower level of responsiveness to anxiety or less perception of temperature induced by maternal separation compared with the WT littermates. WT pups born from aged father exhibited a tendency of decrease in USV calls, which was not statistically different from WT pups born from young father.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that Sey/+ pups born from young father exhibit less vocalization when isolated from their mother and littermates; the phenotype was not obvious in Sey/+ pups born from aged father due to the decreased number of USV calls that occur also in WT littermates. Since USV in pups is considered to be a mother call related to anxiety and perception of temperature [54, 55], Sey/+ pups born from young father may exhibit a lower level of responsiveness to anxiety or less perception of temperature induced by maternal separation compared with the WT littermates. WT pups born from aged father exhibited a tendency of decrease in USV calls, which was not statistically different from WT pups born from young father.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, recent work has shown that the guanylyl cyclase G rGC is both necessary and sufficient for sensing cool temperatures in the Grueneberg ganglion in the mouse nose (Chao et al, 2015). Identification of rGCs as possible thermosensitive proteins in rodents and C. elegans further diversifies the functions of these versatile signaling proteins, and implies that thermosensory roles of these molecules may be conserved across phyla.…”
Section: Discussionmentioning
confidence: 99%
“…We find that co-expression of AFD-rGCs can further shape temperature responses, and that both the extra-and intracellular domains of these rGCs are necessary for their thermosensitive properties. Identification of thermosensitive rGCs in C. elegans provides insight into the mechanisms by which neurons can achieve exceptional thermosensitivity, and together with the recently identified mouse receptor guanylyl cyclase G thermosensory molecule (Chao et al, 2015), may define a new family of evolutionarily conserved thermoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…rGCs are also widely expressed in sensory and other neuron types, and retinal GUCY2D and Grueneberg ganglion GC-G have basal guanylyl cyclase activities similar to GCY-8 (Chao et al, 2015; Shyjan et al, 1992). Increased GUCY2D activity leads to defects in photoreceptor outer segment shape in Leber’s Congenital Amaurosis with some patient mutations mapping to the ECD (Perrault et al, 2000).…”
Section: Discussionmentioning
confidence: 99%